2023
DOI: 10.3390/met14010020
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Uniaxial Compression of Textured Magnesium AZ31B

Lawrence Whitmore,
Anton Nischler,
Holger Saage
et al.

Abstract: Strain-controlled uniaxial compression tests on textured magnesium AZ31B sheet samples were carried out using a 5 kN Kammrath & Weiss tension–compression in situ stage using a scanning electron microscope in combination with real-time electron backscatter diffraction lattice orientation mapping. The distribution of deformation twins in the samples was studied and correlated with the results of finite element simulation of the elastic strain to show that bands of twinned grains formed in areas where the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Figure 3b shows the polished sample fixed using hardened steel gripping plates in the in situ stage. Figure 4c to the minor principal stress σ 3 * as in the uniaxial experiments in [15], although a pure shear stress state prevails. Figure 3d shows the distribution of the minor principal stress σ 3…”
Section: Methodsmentioning
confidence: 85%
See 4 more Smart Citations
“…Figure 3b shows the polished sample fixed using hardened steel gripping plates in the in situ stage. Figure 4c to the minor principal stress σ 3 * as in the uniaxial experiments in [15], although a pure shear stress state prevails. Figure 3d shows the distribution of the minor principal stress σ 3…”
Section: Methodsmentioning
confidence: 85%
“…These bands formed normal to the maximal principal compressive stress σ * 3 and individual twins inside the bands were aligned approximately parallel to those bands. Recent in situ studies of magnesium subjected to uniaxial compressive stress confirmed this and investigated in more detail the initiation and growth of individual twins [15] under this stress state. The current study applies this approach of in situ testing with pure shear stress, an area that has not yet been explored in the literature.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations